Newly initiated carbon stock, organic soil accumulation patterns and main driving factors in the High Arctic Svalbard, Norway - Juselius, Teemu; Ravolainen, Virve Tuulia; Zhang, Hui; Piilo, Sanna; Müller, Mitro; Gallego-Sala, Angela; Väliranta, Minna (Scientific Reports, 2022)
High latitude organic soils form a significant carbon storage and deposition of these soils is largely driven by climate. Svalbard, Norway, has experienced millennial-scale climate variations and in general organic soil processes have benefitted from warm and humid climate phases while cool late Holocene has been unfavourable. In addition to direct effect of cool climate, the advancing glaciers have restricted the vegetation growth, thus soil accumulation. Since the early 1900’s climate has been warming at unprecedented rate, assumingly promoting organic soil establishment. Here we present results of multiple organic soil profiles collected from Svalbard. The profiles have robust chronologies accompanied by soil property analyses, carbon stock estimations and testate amoeba data as a proxy for soil moisture. Our results reveal relatively recent initiation of organic soils across the Isfjorden area. The initiation processes could be linked to glacier retreat, and improvement of growing conditions and soil stabilization. Carbon stock analyses suggested that our sites are hot spots for organic matter accumulation. Testate amoebae data suggested drying of soil surfaces, but the reason remained unresolved. If continued, such a process may lead to carbon release. Our data suggest that detailed palaeoecological data from the Arctic is needed to depict the on-going processes and to estimate future trajectories. Peer reviewed